From Fields to Futures: Examining the Socioeconomic Shifts from Cardamom Cultivation in Eastern Nepal - Budhathoki, Drona (International Research Journal of MMC, 2024)
Large-scale cardamom cultivation in Eastern Nepal is primarily concentrated in six districts, namely Dhankuta, Taplejung, Panchthar, Ilam, Terhathum and Sankhuwasabha, contributing over 80% of the national production and engaging approximately 60,000–70,000 families. The study aims to investigate how cardamom farming has impacted farmers' livelihoods compared to traditional farming methods and how the volatility of cardamom prices underscores the complex dynamics of capitalist market structures. This study focused on Ward No. 2 of Mahalaxmi Municipality in Dhankuta District and spans a five-year period from 2019 to February 18, 2024. Through census-based data collection from 27 households using interviews and observations, the research examined the impact of cardamom production on local livelihoods. The analysis incorporates insights from Marx's Mode of Production, along with perspectives from Jagannath Adhikari, Mark Liechty, and Ian Carlos Fitzpatrick. The findings reveal that earnings from cardamom cultivation did not only elevate living standards but also encouraged self-sufficiency and reduced reliance on foreign employment through borrowing, highlighting changing economic opportunities, self-esteem, and job prospects within the community. The study reveals that cardamom farming has the potential to significantly influence farmers' economic stability and highlights the need for better market strategies and government policies to address price volatility and enhance cardamom productivity.